The dragonet prophecy - Sutherland, Tui T. (Wings of fire, 2012)
Clay has lived his whole life under the mountain. The MudWing dragonet knows war is raging between the dragon tribes in the world outside - a war that he and four other dragonets are destined to end, according to the mysterious prophecy they have been taught. The five "chosen" dragonets were stolen from their homes while they were still in their eggs - and hidden away for years - all to fulfill the prophecy. But not every dragonet wants a destiny. And when danger threatens one of their own, Clay and his friends may choose freedom over fate ... leave the mountain ... and set the dragon world on a course that no one could have predicted.